EVALUASI PENGEMBANGAN SDM PEMERINTAHAN MELALUI PENDIDIKAN DAN PELATIHAN DALAM MENDORONG CORE VALUES ASN BERAKHLAK DI KOTA SURABAYA - Nia Dwi Yuniawanti; Widuri Wulandari (LPPM Universitas Abdurrab, 2025)
The development of human resources (HR) for state civil servants (ASN) is a strategic agenda in promoting bureaucratic reform that is adaptive and based on integrity. This study aims to evaluate the effectiveness of education and training (Diklat) programs in supporting the internalization of ASN BerAKHLAK core values in Surabaya City. The research employs a library research approach by reviewing relevant scientific literature, national regulations, and previous studies to obtain a comprehensive understanding of the issues being examined. The findings indicate that the Diklat program has made a positive contribution to improving ASN competence, work ethic, and professionalism, particularly in the values of public service, accountability, and collaboration. However, the implementation of adaptive and loyal values remains suboptimal, as reflected by low employee initiative, disciplinary violations, and the lack of exemplary leadership. To address these issues, the study recommends strengthening participatory training methods, increasing the intensity of mentoring and coaching, developing technology-based evaluation systems, and fostering cross-sector collaboration to build a more adaptive, disciplined, and service-oriented ASN work culture.